The immune-supportive diet in allergy management: A narrative review and proposal - Vlieg-Boerstra Berber; Groetch Marion; Vassilopoulou Emilia; Meyer Rosan; Laitinen Kirsi; Swain Anne; Durban Raquel; Benjamin Olga; Bottse Rachelle; Grimshaw Kate; Netting Merryn; O'Mahony Liam; et al. (Wiley, 2025)
The role of nutrition is increasingly recognized in the management of chronic immune diseases. However, the role of an immune-supportive diet as adjuvant therapy in the management of allergic disease has not been similarly explored. This review assesses the existing evidence for a relationship between nutrition, immune function, and allergic disease from a clinical perspective. In addition, the authors propose an immune-supportive diet to enhance dietary interventions and complementing other therapeutic options for allergic disease from early life to adulthood. A narrative review of the literature was conducted, to determine the evidence of the relationship between nutrition and immune function, overall health, epithelial barrier function, and gut microbiome, particularly in relation to allergy. Studies on food supplements were excluded. The evidence was assessed and utilized to develop a sustainable immune-supportive diet to complement other therapies in allergic disease. The proposed diet consists of a highly diverse range of fresh, whole, and minimally processed plant-based and fermented foods supplemented with moderate amounts of nuts, omega-3-rich foods and animal-based products in proportional amounts of the EAT-Lancet diet, such as (fatty) fish, (fermented) milk products which may be full-fat and eggs, lean meat or poultry, which may be free-range or organic.